KESALEHAN RITUAL DAN KESALEHAN SOSIAL SISWA MUSLIM SMA DI EKS KARESIDENAN SURAKARTA - AM Wibowo (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
Religious education encompasses two dimensions of human life, namely the cultivation of piety towards God and the development of sense of humanity towards others, or ritual and social piety. But in reality, these two things in education are less integrated so that they become dichotomy and even gap between ritual and social piety. This study is quantitative which aims at measuring and analyzing ritual and social piety of high school Muslim students in the ex-Surakarta Residency based on their gender. The assumption built in this study is that Islamic Education in schools is able to give birth to ritual and social piety of their students. There are two research questions: first, what is the category of ritual and social piety of high school Muslim students at the ex-Surakarta Residency?. Second, what is the difference between ritual and social piety of high school Muslim students at the ex-Surakarta Residency based on their gender?. The null hypothesis (H0) built in this study is: there is no difference between ritual and social piety of male and female Muslim students. By using descriptive analysis and ANOVA test, this study found two things; first, ritual and social piety of high school Muslim students in the ex-Surakarta Residency are good. Second, there is no difference between ritual and social piety in male high school Muslim students. There is difference in ritual and social piety of female students and also difference in ritual and social piety of male and female high school Muslim students in the exSurakarta Residency.